GRP-190 Use of Tranquillisers and Restraint in a French Teaching Acute Care Hospital. (12th March 2013) - Curatolo, N; Colombier, B; Chinet, T; Goeau-Brissonniere, O; Teillet, L; Lemercier, F; Moulias, S
Abstract : Background: Major and minor tranquillisers can be used to chemically restrain a patient. Use of chemical restraint (CR) has been described mainly in long care settings but there is very limited information when considering acute care hospitals. Purpose: To study the prescriptions for major and minor tranquillisers in 3 clinical wards of a French teaching hospital and to determine if they can be considered CR. Materials and Methods: This prospective study took place over 2 weeks in 3 different wards: geriatrics, pneumology and vascular surgery. Tranquilizers were defined as anxiolytics (minor) and neuroleptics (major). Prescriptions were checked daily and for each patient with a tranquilliser, medical records were screened to determine whether it was newly prescribed. For every newly-prescribed tranquilliser the practitioner was asked the indication, if he considered his prescription was a CR and if the patient was being physically restrained. Results: 45.2% of the 137 patients included had been prescribed at least 1 tranquilliser. 54.5% of the 77 tranquillisers prescribed were introduced during the hospitalisation. Among those 42 newly-introduced tranquillisers, 9 (21.4%) were considered as CR by the prescribers. 6.6% of the patients included were chemically restrained, which is comparable with previous retrospective studies of restraint in acute care wards. The most frequently prescribed CR was alprazolam (55.6%) and the most frequent indication for CR was anxiety. In addition 88.9% of the CR drugs were prescribed 'when required' leaving responsibility for administration to nurses alone. None of the patients with tranquillisers had physical restraint. Conclusions: This is the first prospective study on restraint in an acute care hospital. CR is used for a minority of patients; however it is mostly prescribed 'when required'. Hence it should be used with the utmost care and prescribed with the most precise instructions in order to avoid misuse and risk of abuse. No conflict of interest.